2018
DOI: 10.3389/fpsyt.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

eHealth in Treatment of Offenders in Forensic Mental Health: A Review of the Current State

Abstract: BackgroundTreatment of offenders in forensic mental health is complex. Often, these in- or outpatients have low treatment motivation, suffer from multiple disorders, and have poor literacy skills. eHealth may be able to improve treatment outcomes because of its potential to increase motivation and engagement, and it can overcome the predominant one-size-fits-all approach by being tailored to individual patients.ObjectiveTo examine its potential, this systematic review studies the way that eHealth has been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(114 citation statements)
references
References 84 publications
0
103
0
Order By: Relevance
“…Although mHealth technologies can help to provide objective EMA recordings, they also have some difficulties. For instance, the high cost of development and maintenance for mHealth Apps, the lack of standardization, data management, technical problems, slow connections, and so on are possible problems that should be borne in mind (128). In addition, mEMA devices could be expensive if they are only used for research purposes.…”
Section: Limitationsmentioning
confidence: 99%
“…Although mHealth technologies can help to provide objective EMA recordings, they also have some difficulties. For instance, the high cost of development and maintenance for mHealth Apps, the lack of standardization, data management, technical problems, slow connections, and so on are possible problems that should be borne in mind (128). In addition, mEMA devices could be expensive if they are only used for research purposes.…”
Section: Limitationsmentioning
confidence: 99%
“…A recent systematic review pointed out that technology can be of added value for patients, therapists and the quality of care in forensic mental health in multiple ways [14]. This review included 50 studies that focused on a broad range of technologies, for example web-based interventions, serious games, videoconferencing, social platforms and virtual reality.…”
Section: Background and Related Work Technology And Forensic Mental Hmentioning
confidence: 99%
“…Furthermore, multiple studies found that therapists and even patients often have a positive attitude towards working with technologies such as VR in treatment, which might increase the usually low treatment motivation of patients [10]. Also, an important benefit of technology is that it can be tailored to individual patient characteristics to overcome a one-size-fits-all approach that does not fit the diverse forensic patient population [14]. A technology which has characteristics that are aligned with these benefits is virtual reality.…”
Section: Background and Related Work Technology And Forensic Mental Hmentioning
confidence: 99%
See 2 more Smart Citations